2020
DOI: 10.1136/jitc-2020-001377
|View full text |Cite
|
Sign up to set email alerts
|

2,5-dimethylcelecoxib improves immune microenvironment of hepatocellular carcinoma by promoting ubiquitination of HBx-induced PD-L1

Abstract: Background2,5-dimethylcelecoxib (DMC) is a targeted inhibitor of microsomal prostaglandin E synthase-1 (mPGES-1), a key enzyme in the PGE2 synthesis pathway of inflammatory mediators. Previous studies have confirmed that DMC can inhibit the growth of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). However, it is not known whether DMC is involved in the changes of tumor immune microenvironment.MethodsIn this study, we explored the effects of DMC on HBV-related HCC immune microenvironment, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Numerous studies have shown that PD-1 is the main and key inhibitory receptor in tumor immunity. Immunotherapy aimed at blocking PD-1 and its ligand (PD-L1) has become an important means of treating tumors ( Chen Z. et al, 2020 ). It is precisely because we did not find significant differences in the detection of PD-L1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that PD-1 is the main and key inhibitory receptor in tumor immunity. Immunotherapy aimed at blocking PD-1 and its ligand (PD-L1) has become an important means of treating tumors ( Chen Z. et al, 2020 ). It is precisely because we did not find significant differences in the detection of PD-L1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Siyuan Ding found that siRNA knockdown and chemical inhibition of the activity of Rbx1 could suppress the degradation of β-TrCP mediated by RV encoding non-structural protein 1 (NSP1), which was beneficial to the activation of NF-κB signaling pathway, effectively reducing the ability of NSP1 to mount an antagonistic host immune response and inhibiting virus reproduction [ 51 ]. Rbx1 is also associated with the antitumor DMC that can improve the immune microenvironment of hepatocellular carcinoma cells [ 52 ]. ISG15 , which was wildly studied in immune processes, is a 15 kDa ubiquitin type I IFN that stimulates proteins and has various functions, such as activating immune cells, inducing the secretion of cytokines, and acting as a mediator of the immune response [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that 2,5-dimethylcelecoxib (DMC), a targeted inhibitor of mPGES-1, could enhance ubiquitin-mediated degradation of HBxinduced PD-L1 protein in HCCs. 135 Further evidence demonstrates that this process is mainly regulated by E3 ligase RBX1. 135 Moreover, the small molecule WP1130, a selective deubiquitinase suppressor, attenuates the deubiquitinating potential of several DUBs, including USP5, USP9X, USP14, and USP37.…”
Section: Targeting E3 and Dubs To Enhance Pd-1/pd-l1 Therapymentioning
confidence: 99%
“…135 Further evidence demonstrates that this process is mainly regulated by E3 ligase RBX1. 135 Moreover, the small molecule WP1130, a selective deubiquitinase suppressor, attenuates the deubiquitinating potential of several DUBs, including USP5, USP9X, USP14, and USP37. WP1130 has been demonstrated to effectively inhibit cancers by triggering aggresome formation and promoting cancer cell apoptosis and chemosensitivity.…”
Section: Targeting E3 and Dubs To Enhance Pd-1/pd-l1 Therapymentioning
confidence: 99%